Postnatal choline supplementation selectively attenuates hippocampal microRNA alterations associated with developmental alcohol exposure - Balaraman, Sridevi; Idrus, Nirelia M.; Miranda, Rajesh C.; Thomas, Jennifer D. (Alcohol (Fayetteville, N.Y.), 2017)
Prenatal alcohol exposure can result in a range of physical, neuropathological, and behavioral alterations, collectively termed fetal alcohol spectrum disorders (FASD). We have shown that supplementation with the nutrient choline reduces the severity of developmental alcohol-associated deficits in hippocampal-dependent behaviors and normalizes some aspects of hippocampal cholinergic development and DNA methylation patterns. Alcohol's developmental effects may also be mediated, in part, by altering microRNAs (miRNAs) that serve as negative regulators of gene translation. To determine whether choline supplementation alters ethanol's long-lasting effects on miRNAs, Sprague-Dawley rats were exposed to 5.25 g/kg/day ethanol from postnatal days (PD) 4–9 via intubation; controls received sham intubations. Subjects were treated with choline chloride (100 mg/kg/day) or saline vehicle subcutaneously (s.c.) from PD 4-21. On PD 22, subjects were sacrificed, and RNA was isolated from the hippocampus. MiRNA expression was assessed with TaqMan Human MicroRNA Panel Low-Density Arrays. Ethanol significantly increased miRNA expression variance, an effect that was attenuated with choline supplementation. Cluster analysis of stably expressed miRNAs that exceeded an ANOVA p < 0.05 criterion indicated that for both male and female offspring, control and ethanol-exposed groups were most dissimilar from each other, with choline-supplemented groups in between. MiRNAs that expressed an average 2-fold change due to ethanol exposure were further analyzed to identify which ethanol-sensitive miRNAs were protected by choline supplementation. We found that at a false discovery rate (FDR)-adjusted criterion of p < 0.05, miR-200c was induced by ethanol exposure and that choline prevented this effect. Collectively, our data show that choline supplementation can normalize disturbances in miRNA expression following developmental alcohol exposure and can protect specific miRNAs from induction by ethanol. These findings have important implications for the mechanisms by which choline may serve as a potential treatment for FASD. •Developmental alcohol exposure dysregulates hippocampal miRNA expression.•Developmental alcohol exposure specifically increases several miRNAs.•Choline supplementation normalized ethanol-related increases in miRNA variance.•Choline specifically attenuated ethanol-related increases in hippocampal miR-200c.•Choline may reduce fetal alcohol spectrum disorders by altering miRNAs.